Leadership Personality Traits of Physical Educators from Secondary School Administration Point of View In Baghdad / Al Resafa Directorates - Tariq, Eyad; Radhi, Saleh (Journal of Physical Education, 2019)
The aim of the research is designing a leadership personality traits scale for physical educators from secondary school administration point of view in Baghdad / Al Resafa Directorates as well as identifying the level of leadership trait level for physical educators from secondary school administration point of view in Baghdad / Al Resafa Directorates. The researchers used the descriptive method on (327) secondary schools in Baghdad/ Al Rasafa directorates; the subjects were (420) principles and assistant principals of secondary schools. The researchers proposed (25) item for measurement and after being revised by experts 20 items were approved and applied on (180)construction subject followed by (100) research subjects. The results of the research show an attitude towards sport privatization in primer soccer league.